An Improved Immersed-Boundary Algorithm for Fluid-Solid Interaction un Lattice-Boltzmann Simulations - Boroni, Gustavo Adolfo (2013)
An improved algorithm combining the features of the lattice Boltzmann and the immersed-boundary methods is presented. Following previous formulations, the method represents a fluid con-strained by flexible boundaries by means of a force term acting on the cells adjacent to the boundary, which in turn is moved by the fluid. The present al-gorithm introduces a more efficient iteration proce-dure to calculate the fluid-boundary interaction, which facilitates the implementation. The simulations where validated against experimental and analytical data showing good agreement and demonstrating the performance of the method to simulate different kind of fluid-solid interaction.